P USE EFFICIENCY BY CORN (Zea mays L.) IN ULTISOL DUE TO APPLICATION OF COAL FLY ASH-CHICKEN MANURE MIXTURE - Hermawan, Agus; Sabaruddin, Sabaruddin; Marsi, Marsi; Hayati, Renih; Warsito, Warsito (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2014)
Low P availability is the main constraint for crops on acidic soil such as an Ultisols due to high soil P sorption. The objective of current research was to determine the effect of coal fly ash-chicken manure mixture application on P use efficiency by corn (Zea mays L.) in Ultisols. The research were arranged according to Factorial Completely Randomized Design with three replicates. The treatments tested were the rates of FA-CM mixture (w/w of 1:1) that consisted of 0, 15, 30, 45 and 60 tons ha-1, and P fertilizer rates that consisted of 0, 0.5, 1.0, 1.5 and 2.0 times of P requirement to achieve of 0.2 μg P mL-1 in soil solution (equivalence to 0, 87, 174, 261 and 348 kg P2O5 ha-1). Results of current research showed that P use efficiency by corn on Ultisols had been increased through the addition of FA-CM in combination with P fertilization at the rate of 87 kg P2O5 ha-1. The optimum rate of FA-CM in combination with P fertilizer at the rate of 87 kg P2O5 ha-1 is 28.60 tons ha-1, with P uptake efficiency of 42.41 % and agronomic P efficiency of 82.53 mg shoot dry weight/mg P from fertilizer.